Validation and implementation of a modular targeted capture assay for the detection of clinically significant molecular oncology alterations - Kuo, Ayako J.; Paulson, Vera A.; Hempelmann, Jennifer A.; Beightol, Mallory; Todhunter, Sheena; Colbert, Brice G.; Salipante, Stephen J.; Konnick, Eric Q.; Pritchard, Colin C.; Lockwood, Christina M. (Practical laboratory medicine, 2020)
The rapid discovery of clinically significant genetic variants has translated to next-generation sequencing assays becoming out-of-date by the time they are designed, validated, and implemented. UW-OncoPlex addresses this through the adoption of a modular panel capable of redesign as significant alterations are identified. We describe the validation of OncoPlex version 6 (OPXv6) for the detection of single nucleotide variants (SNVs), insertions and deletions (indels), copy number variants (CNVs), structural variants (SVs), microsatellite instability (MSI), and tumor mutational burden (TMB) in a panel of 340 genes. One hundred twelve samples with diverse diagnoses were comprised of formalin-fixed-paraffin-embedded tissue, fresh-frozen tissue, plasma, peripheral blood, bone marrow, saliva, and cell-line DNA. Libraries were prepared from genomic and cell-free DNA, hybridized to a custom panel of xGen Lockdown probes, and sequenced on Illumina platforms. Sequences were processed through a custom bioinformatics pipeline, and variant calls were compared to prior orthogonal clinical results. Accuracy was 99% for SNVs ≥5% allele frequency, 98% for indels, 97% for SVs, 99% for CNVs, 100% for MSI, and 100% for TMB (compared to previous OncoPlex versions). Library preparation turnaround time decreased by 40%, and sequencing quality improved with a 2.5-fold increase in average sequencing coverage and 4-fold increase in percent on-target. OPXv6 demonstrates improvements over prior UW-OncoPlex versions including reduced capture cost, improved sequencing quality, and decreased time to results. The modular capture probe design also provides a nimble laboratory response in addressing the expansions necessary to meet the needs of the continuously evolving field of molecular oncology. •OncoPlex version 6 is a targeted, comprehensive next generation sequencing panel.•The panel of 340 genes includes full coverage of BRCA1/2 and mismatch repair genes.•While sequencing quality increased, library preparation time and cost decreased.•The panel is modular and capable of rapid redesign and expansion of targeted genes.